2017
DOI: 10.5430/jha.v6n3p58
|View full text |Cite
|
Sign up to set email alerts
|

Intention to leave among health care professionals: The importance of working conditions and social capital

Abstract: Hospitals in Sweden are redesigning their care processes to increase efficiency. However, related to these changes, there is a risk of increased staff intention to leave and turnover due to increased workload and work pace. The literature on work engagement and job demands and resources suggests that specific job resources can buffer negative effects; i.e., intention to leave because of job demands. Social capital is suggested to have the potential to be a resource associated with staff intention to leave. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…It can also be considered specifically important to develop functional resources supporting younger nurses as previous research show that they have higher degrees of intentions to leave (Flinkman et al., 2010). The results specifically point to the importance of developing social capital as an organizational resource for staff retention in healthcare organizations, which is in line with other research showing the importance of social capital for healthcare professionals' engagement and job satisfaction (Strömgren, 2017a).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It can also be considered specifically important to develop functional resources supporting younger nurses as previous research show that they have higher degrees of intentions to leave (Flinkman et al., 2010). The results specifically point to the importance of developing social capital as an organizational resource for staff retention in healthcare organizations, which is in line with other research showing the importance of social capital for healthcare professionals' engagement and job satisfaction (Strömgren, 2017a).…”
Section: Discussionsupporting
confidence: 89%
“…Resources at work that are associated with nurses' intentions to leave embrace general perceptions of resources in the work environment (Chan et al., 2013). Specific resources that have been identified affecting nurses intention to leave include influence at work, possibilities for development (Carter & Tourangeau, 2012; Hayes et al., 2012; Tummers et al., 2013), interprofessional collaboration, leadership practices (Choi et al., 2013), support from managers and colleagues (Hasselhorn et al., 2005; Hayes et al., 2012; Ito et al, 2001), recognition and predictability (Strömgren, 2017a). These resources have thus been included in this study as job resources which are potentially associated with nurses' intention to leave (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of a direct effect does not detract from our main finding of social capital playing a role in early filling failure through job satisfaction, because the approach to testing mediation does not require (mathematically or theoretically) a significant direct pathway from the predictor to the outcome. Overall, our main finding corroborates previous research, which has found that social capital leads to job satisfaction [ 8 , 11 13 , 19 ] and to better self-reported performance [ 8 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted in 2017 showed that social capital includes co-workers' or employees' relationships with their supervisors directly affecting job satisfaction which would influence intention to resign [32]. Professional relationships in workplace is a factor in job satisfaction that is believed to contribute to job performance and employee commitment.…”
Section: Intention To Leavementioning
confidence: 99%